Development of Mathematics Enrichment Program Using Community-Based Learning for Lower Secondary School Level, Ban Siao School - Chottirattanakul, Varaporn; Mahavijit, Pongsatorn; Pilanthananond, Nataya (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2022)
This research aims to develop and evaluate the effectiveness of mathematics enrichment program using community-based learning for lower secondary school level, Ban Siao School. The sample of this research includes 26 students of Ban Siao School at lower secondary school level, voluntarily join this program. Research instruments include pre and post-test, satisfaction questionnaire towards the enrichment mathematics program. The data were analyzed by using percentage, means ( ) and standard deviation (S.D.) and t-test. The results of the research Enrichment mathematics program 5 units elements include 1) The goal of the curriculum 2) The aim of the curriculum 3) Content structure 4) The learning activities 5) The media and learning resources and 6) The evaluation and assessment of learning. Students had different achievements and significant pre and post- training scores at .05. The post-test scores were higher than that of the pre-test scores at 32.77>11.35. Their satisfaction highest level ( =3.21, S.D.=0.54) and applying mathematical content in daily life were at the highest level ( =3.38, S.D.=0.49)